EFEKTIVITAS MODEL PEMBELAJARAN TTW (THINK TALK WRITE) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SD NEGERI 2 PENENGAHAN BANDAR LAMPUNG - Rahmawati, Fitriana (STKIP PGRI Bandar Lampung, 2021)
This study aims to analyze and determine the effectiveness of the TTW (Think Talk Write) learning model on the mathematical problem solving abilities of SD Negeri 2 Penengahan Bandar Lampung students. This research is an experimental research. The study population consisted of all students of class SD Negeri 2 Penengahan Bandar Lampung consisting of 5 classes with a total of 120 students, while 2 classes were taken as samples, namely class V A as the experimental class which consisted of 32 students, and class V C as the control class which consisted of 30 students. The sample was taken using the Cluster Random Sampling technique. Students' mathematical problem solving abilities were measured by a test in the form of an essay of 5 questions which had previously been tested for validity and reliability. From the results of testing the hypothesis using the statistical formula t-test, the value of thit = 2.15 was obtained. From the t distribution table at a significant level of 5%, it is known that tdaf=1.67 means thit>tdaf, namely 2.15>1.68, so it can be concluded that